Detection of Dengue Serotypes by Two Molecular Techniques, qPCR and LAMP (TAJ: Journal of Teachers Association, 2021)
Background: Dengue virus is a mosquito-borne flavivirus and the most widely prevalent arbovirus in tropical and subtropical regions. Detection of this virus by a new molecular technique named Loop-mediated isothermal amplification (LAMP) is a very sensitive, easy, and less time-consuming diagnostic method. It can amplify up to 109 copies in less than 1 hour under isothermal conditions (65°C).Aims: To establish a dengue LAMP as simple, less time-consuming, more specific, and sensitive than the qPCR to detect dengue serotypes.Materials and Methods: This prospective analytical study was conducted from January- December 2017 at the Department of Virology, BSMMU, Dhaka, Bangladesh. A total of 290 serum samples were used, confirmed by ICT (immune chromatographic test). These samples were used to perform qPCR for the detection of dengue serotypes. After that, dengue LAMP was performed using the same samples to establish the LAMP technique as a suitable, time-saving molecular technique that is more sensitive than qPCR.Results: A total of 290 dengue confirmed samples by ICT were used for qPCR to detect dengue serotypes. Among which 137 dengue I and 113 dengue II RNA positive serum samples were confirmed by qPCR, and those were also positive by LAMP assay. Besides, 20 both dengue NS1 and dengue IgM negative by ICT were tested by qPCR, and 01 positive dengue II serotype was detected by qPCR, whereas 02 dengue II serotypes were detected by dengue LAMP technique from the same samples.Conclusion: RT-LAMP assay had been developed in this study which allowed the rapid and accurate identification of dengue virus serotypes.TAJ 2021; 34: No-1: 01-04